Kaidah Penafsiran Puisi Perjanjian Lama - Paulus Dimas Prabowo (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2021)
God who is so creative not only used various types of people to write His revelations but also used various types of literature (genre) known in human civilization. That is why, the methods of studying and analyzing a text may differ from one another, depending on the type of literature. Recently, the results of biblical research have looked at the type of literature as the main consideration in finding the meaning. The same thing should also be adopted by biblical researchers in this country. This article aims to explain how to analyze biblical texts in the genre of Old Testament poetry. Because it is not uncommon for students to find poetry book Bibles with improper procedures. Writing poetry is not the same as telling stories about narrative, epistolary, and other genres. Therefore, the writer tries to present a way to analyze the Old Testament poetry books, in order to equip the readers with the right procedure in capturing the Old Testament poetry texts. The method used in this article is to find a literature study, where the data in this article were obtained from various sources with related topics.Allah yang begitu kreatif tidak hanya memakai beragam jenis orang untuk menuliskan wahyu-Nya, tetapi juga memakai bermacam jenis sastra (genre) yang dikenal dalam peradaban manusia. Itu sebabnya, metode dalam mempelajari dan menganalisa sebuah teks bisa berbeda satu sama lain, tergantung jenis sastranya. Belakangan, hasil-hasil penelitian biblika telah melirik jenis sastra sebagai pertimbangan utama dalam menggali dan menemukan makna. Hal senada juga seyogyanya dianut oleh para peneliti biblika di negeri ini. Artikel ini bertujuan untuk menjelaskan bagaimana menganalisis teks alkitabiah dalam genre puisi Perjanjian Lama. Sebab, tidak jarang pelajar Alkitab menggali buku puisi dengan prosedur yang tidak semestinya. Cara penggalian kitab puisi tidak sama dengan cara penggalian kitab narasi, epistolari, dan genre lainnya. Oleh karena itu penulis mencoba menyajikan suatu cara untuk menganalisis kitab-kitab puisi Perjanjian Lama, guna membekali pembaca dengan prosedur yang tepat dalam menggali teks-teks puisi Perjanjian Lama. Metode yang dipakai dalam artikel ini ialah studi literatur, di mana data-data dalam artikel ini diperoleh dari beragam sumber dengan topik terkait.